KEANEKARAGAMAN JENIS TUMBUHAN HERBA PADA DUA TIPE HUTAN DI DESA BOBO KAWASAN TAMAN NASIONAL LORE LINDU SULAWESI TENGAH - Mohammad Iqbal N. Laratu; Ramadhanil Ramadhanil; Samsurizal M. Suleman (Biology Department, Mathematics and natural science, Tadulako University, 2014)
The title of this research is “Herbs plant species diversity at two forest types of Lore Lindu National Park at Bobo village in Central Sulawesi. This research was conducted on May to July 2013. The objective of this research was to learn and to know about, diversity of herbs species at two forest types at Bobo village Lore Lindu National Park of Central Sulawesi. The type of this research is exploratory survey research by using the establishment of a single plot (50 x 50 m) followed by subplot (2 x 2 m) were placed on regular basis (systematic). The results of this research showed that there were sixteen (16) species of herbs plant in primary forest and twenty two (22) species in secandary forest. The Aglaonema simplex Blume (Araceae) was highest IVI of herb in primary forest (42.03%), the other hand Tacca palmata Blume (Taccaceae) was highest in secandary forest (38.80%). The value of Similarity Indeks between two forest types studied was 69.04%. Based on the FIV Index the primary forest and secandary forest were dominated by Araceae. Keywords : Herbs, The Village of Bobo, Lore Lindu National Park, Central Sulawesi.